Towards sustainable agricultural water management in Poland – How to meet water demand for supplemental irrigation? - Paweł Marcinkowski; Mikołaj Piniewski; Tomasz Okruszko (Agricultural Water Management)
The global challenge of water scarcity, particularly in agriculture, demands urgent attention due to the overexploitation of water resources and the escalating impacts of climate change. This study focuses on the unique challenges faced by Poland, experiencing increasing concerns related to droughts. It explores the utilization of supplemental irrigation, specifically in the context of Central Europe, where a distinctive approach known as supplemental irrigation is employed. The study emphasizes the need for sustainable water management practices and investigates the potential of small water retention measures (SWRMs), such as ponds and drainage water management, as solutions to enhance water availability in agriculture. A macro-scale water balance study is conducted using the Soil and Water Assessment Tool (SWAT) to estimate spatio-temporal variability of water demand for supplemental irrigation in Poland. The highest demand, approximately 2.5 billion m3 (for arable lands) and 1.3 billion m3 (for grasslands), occurred during the exceptionally dry year of 2015, characterized by severe agricultural drought effects. The study also assesses the efficiency of SWRMs in meeting irrigation demands at national level. The results highlight a paradox in their effectiveness during critical periods, specifically in dry years when water demands are the highest. The outcomes of the model experiment underscored concerns about the insufficiency of meeting the water needs of irrigated agriculture solely through the construction of small retention facilities during very dry years. The outcomes of this research contribute to a better understanding of irrigation water demands in temperate climate region, support evidence-based practices for sustainable water management, and inform policymakers and stakeholders involved in water governance.